Formación ciudadana (FC) y Educación para la ciudadanía (EpC). Aproximaciones conceptuales y mínimos compartidos (2011)
ABSTRACT: The paper gives an account of advances in research related to conceptual references of the doctoral thesis ofthe authors. The current paper was the conceptual approach about a common preoccupation: the field that establishesthe relationship between citizenship development (CD) and education for citizenship (EC). Consequently,this article deals with that relationship, not to close the discussion but instead to open it. This writing warns aboutthe urgent need of setting the theoretical basis of this growing field that today has become as one of the broadesteducational speeches on the social and political environment.With that goal in mind, the initial argument for this discussion is the evidence that regardless the heterogeneityof the above mentioned theoretical frames, a common field of thought may be identified between them. In fact, later on in the article, it is discussed the concept about the relationship between formation and education thatgives rise to the problem pointed out here as CD and EC, in order to finally, propose as a mode of balance, someanalytical dimensions that could guide the debate that contributes to the foundation of this field.